Tathwîru dzkâât al muta‘addidah bi alansyithah al idhafiyah lithâlibât al fashli al khamisi bi ma‘ahadi dârissalâm guntûr li albanât alharam atsâlits li attarbiyyah al islâmiyyah al hadîtsah - Noor Syahid; Anisa Jaya Rahmawati; Fairuz Subakir (At-Ta'dib, 2018)
The theory of multiple intelligences have the point of appeal among the other disciplines, because theory of multiple intelligences integrated traditional concept and reasoning to achieve goals in  future. The variety of mutiple Intelligences likely: linguistic intelligence, logical-mathematic intelligence, visual intelligence, kinestetic body intelligence, musical intelligence, interpersonal intelligence, intrapersonal intelligence and natural intelligence. The type of this research is qualitative descriptive, whether in the analysis using data collection, presentation of data and conclusion. Gontor always tries to develop its linguistic intelligences for fifth grade trough discussion, practice the speech and afternoon lesson. These activities develop capability to make sentences, capability to read and write by grammar, capability to write and read by systematically and logically, capability to speak in general public, and capibility to give opinions. Other Interpersonal Intelligences development for fifth grade are Student Organization and discussion. These activities develop capability to resolve problems, capability to socialization, and leadership. Finally the Intrapersonal Intelligences development includes art exhibition, branch management, discussion and basic leader course. These activities develop capability to regulate emotions, capability to understand persons, capability to socialization, capability to resolve problems, capability to place ourself, capability to manage time, capability to independence and leadership.